Determination of 11 minerals in children using inductively coupled plasma mass spectrometry - Xiaofeng Li; Chunnan Wang; Yang Wang; Xusheng Zhao; Na Li (BMC, 2021)
Abstract Background Minerals play an important role in children's growth and cognition. In this study, our aim was to establish reference intervals of mineral level in Children of Liaoning province (China) and provide a reliable basis for future preventive healthcare guidelines. Methods Random samples of 2217 healthy children aged 0-15 years who were referred for routine hospital laboratory examinations in the cities of Shenyang, Fushun, Fuxin, Benxi, Chaoyang and Lingyuan were invited to participate in the study. Serum levels of Calcium (Ca), Iron (Fe), Zinc (Zn), Magnesium (Mg), Copper (Cu), Manganese (Mn), Selenium (Se), Mercury (Hg), Nickel (Ni), Cobalt (Co), and Lithium (Li) were determined by inductively coupled plasma mass spectrometer(ICP-MS). Results Sex-related significant differences in the serum concentrations of the Mg and Cu (P < 0.05). Age-related significant differences were found in serum levels of Ca, Fe, Zn, Mg, Cu and Mn (P < 0.05) and the concentrations of 9 minerals (Ca, Mg, Cu, Mn,Se,Hg,Ni,Co and Li in serum varied from season to season (P < 0.05). The Spearman correlation matrix of 11 minerals was shown as a heat map, the correlations between Ca-Zn, Ca-Mg, Fe-Zn, Fe-Se, Mn-Ni, Se-Hg, Se-Ni, Hg-Ni, and Ni-Co, Ni-Li were the strongest compared with others. Conclusions The reference intervals of serum 11 minerals for children should considering the sex, age and season, which may be useful for decisive diagnoses of abnormality of the 11minerals and the related diseases.